Connection Over Correction: Engaging Students in Conversational Commitments for Effective Communication Across Difference and Difficulty - Jennifer Sandoval (Central States Communication Association, 2021)
In light of a national reckoning with racism in the U.S., many instructors are assessing their own pedagogical practices with regard to handling these topics in their classrooms. In developing my authentic teaching philosophy over the course of 18 years, I have adapted many practices I used in my prior career in dispute resolution. To clarify, I center classroom engagement around what Hart (2007) describes as "a pedagogy of interiority." Classroom engagement focuses on connection rather than correction as we help students develop their "authentic inner potentials" (p. 2). I regularly challenge myself to invite students to develop their authentic personal selves via contemplation and reflexivity. In doing so, we move from a teacher-centered focus to a student-centered one derived from a relational partnership with them. By focusing on connection rather than correction, we create an environment of curiosity, compassion, and intensive reflection where students come to know themselves and their strengths in ways that extend beyond the classroom. This essay highlights how students co-create conversational commitments coupled with a rapid debrief process that moves my students forward together toward shared mindfulness in thought and behavior.